Penggunaan Herbisida untuk Pengendalian Gulma pada Budi Daya Kedelai Jenuh Air di Lahan Pasang Surut - Perkasa, Achmad Yozar; Ghulamahdi, Munif; Guntoro, Dwi (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Weed is a problem on the soybean saturated culture in tidal swamp land. The objective of this study was to obtain the most effective herbicide for weed control on soybean planted under saturated culture in the tidal swamp land. Research was conducted in tidal swamp land at Banyu Urip village, Tanjung Lago districs, Banyuasin, South Sumatra Province, from July to December 2013, using a randomized block design consisted, of the eight treatments, with three replications. The treatments were: control (P0), manual weeding 4 weeks after planting (P1), paraquat 2 l/ha 4 weeks after planting (P2), glyphosate 3 l/ha 4 after planting (P3), oxyfluorfen 2 l/ha 3 days before planting (P4), oxyfluorfen 3 days before planting 2 l/ha followed application of paraquat 4 weeks after planting 2 l/ha (P5), oxyfluorfen 3 days before planting 2 l/ha followed application of glyphosate 4 weeks after planting 3 l/ha (P6), penoxulam 1 l/ha 2 weeks after planting (P7). Results showed that herbicide paraquat effectively suppressed total dry weight of weeds at 4, 6, and 8 weeks after planting. Cyperus iria was the most dominant weed in the field, with Sum Dominance Ratio 37.7%. The highest soybean productivity was 3.7 t/ha obtained from glyphosate treatment. Pre-emergence herbicide applications should be done prior to soybean planting and the post-emergence herbicide application must be done carefully by using nozzle lid to prevent toxicity to the crop plants.